Panorama ambiental das áreas verdes intraurbanas nos municípios da região metropolitana de Ribeirão Preto através de inteligência geoespacial - Melo, Breno Malheiros de (Universidade Federal de São Carlos, 2025)
The present research aims to analyze urban expansion and the transformations in urban green areas within the Metropolitan Region of Ribeirão Preto (RMRP). It leverages the principles of geospatial intelligence and incorporates technological innovations such as cloud computing, remote sensing, and machine learning. This study is driven by the rapid global urban growth, which can lead to significant environmental impacts, including increased greenhouse gas emissions and environmental degradation. This underscores the crucial importance of developing sustainable and resilient cities, requiring new approaches to monitor and understand urban environmental dynamics. The research focuses on the accurate identification of green areas within the RMRP, the historical reconstruction of changes in urban green spaces through remote sensing, the assessment of the impact of these areas on the regional urbanization process, and the exploration of how the resulting data can support integrated regional planning. The study places particular emphasis on urban areas and environmentally vulnerable zones, such as conservation units and aquifer recharge areas.
Environmental overview of intra-urban green areas in the municipalities of the Ribeirão Preto metropolitan region through geospatial intelligence
Keywords: Região Metropolitana de Ribeirão Preto; Urbanização; Sensoriamento Remoto; Google Earth Engine; Random Forest; Landsat; CIENCIAS EXATAS E DA TERRA; 11. Cidades e Comunidades Sustentáveis